Incidence of mites in the pod rot in two varieties of rice (Oryza sativa L.) - Durán Mera, Christian Alejandro (2021)
Pod rot caused by Sarocladium oryzae is a disease that affects rice cultivation (Oryza sativa L.), it is related with the presence of the Steneotarsonemus spinki mite and excessive applications of nitrogen since in high quantities it attracts the mite. The objective was to determine the mite population in two varieties of rice under the incidence of pod rot, nitrogen fertilization plus application with and without acaricide, plus yield. A divided plot design was used with two varieties of rice, three doses of nitrogen and two applications of acaricide, which totaled 12 treatments with three repetitions for a total of 36 plots evaluated. The variables were numbers of tetranychids, predators and tarsonemids, percentages of spikes affected and yield kg·ha-1. The results showed that the highest number of mites found were 124 predators in three evaluations carried out, the percentage of spikes affected 12% and yields exceeded 2500 kg·ha-1, in addition, the presence of the disease could not be related to the S. spinki mite due to because only one individual was found.